2001
DOI: 10.1089/10915360152745830
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Model To Predict Biochemical Failure After Radical Prostatectomy

Abstract: These results suggest that ANN models can predict PSA failure using readily available preoperative variables. Such predictive models may offer assistance to patients and physicians deciding on definitive therapy for CaP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Logistic regression analysis maximized performance in the training sets only to be outperformed by the ANNs in testing sets. In other articles [18][19][20] the ability of ANNs to assess the preoperative risk of progression was similarly shown.…”
Section: Anns In Predicting Biochemical Failurementioning
confidence: 87%
“…Logistic regression analysis maximized performance in the training sets only to be outperformed by the ANNs in testing sets. In other articles [18][19][20] the ability of ANNs to assess the preoperative risk of progression was similarly shown.…”
Section: Anns In Predicting Biochemical Failurementioning
confidence: 87%
“…Our results agree with those reported in other urological reports supporting the satisfactory diagnostic and prognostic performance of ANNs. Most trials have been focused on prostate cancer, but occasionally ANNs were applied to diagnostic and prognostic problems of kidney, testicle or bladder tumours [9,11–33]. In these studies ANNs were an optimal analytical statistical method to analyse complex problems, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…acute myocardial infarction and pulmonary embolism [7] . In oncological urology ANNs have been investigated specifically to resolve the diagnostic, staging and prognostic problems of prostate cancer, with very promising results [11–24]. Conversely, studies exploring the use of ANNs for kidney, testicle and bladder cancers are uncommon [25–33] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“… 25 Some studies have verified that ANN models have the ability to improve prognosis prediction for PCa patients after prostatectomy. 7 10 26 27 28 29 These data have been summarized in Table 5 . One of the first studies in 1994 demonstrated 87% accuracy.…”
Section: Discussionmentioning
confidence: 99%